Polonia of Kazakhstan Yesterday and Today: Features of Cultural Interaction (Cultural Context): Казахстанская Полония вчера и сегодня: особенности культурного взаимодействия (культурологический контекст) - Sultanova, Madina (Przegląd Wschodnioeuropejski, 2019)
The article presents a culturological interpretation of more than eighty years of cultural development of Polish community of thousands in Kazakhstan. Currently, the republic has developed a unique format of balanced political, economic and socio-cultural interaction of more than one hundred and forty ethnically diverse groups forming the “people of Kazakhstan”. The historical special aspects of the Kazakhstan’s Polonia formation have long been of interest to domestic scientists; however, in practice the cultural context of its existence has not been studied. Works of Kazakh and Russian historians, fact-based material: in-depth interviews with ethnic Poles, representatives of the Center for Polish Culture (Almaty) and other governmental and public organizations that are directly involved in promoting the Polish culture in Kazakhstan establish the article’s theoretical framework. The lookback study and comparative historical method were used when working on the article. According to the authors, the article will provide the analysis of the cultural experience of the Kazakhstan’s Polish diaspora, that can demonstrate the actual state of things and outline the prospects for the further development of the modern multi-ethnic state.